Lugares e imaginarios sociales de La Plaza Grande del Centro Histórico de Quito - Lincango Moreno, María Raquel (2014)
The increasing development of the city has allowed the dissemination of imaginary, which now have become as individual situations are experienced in public spaces in cities. This research was an exploratory analysis of the social imaginary and places of the Plaza de la Independencia de Quito, allowed to determine how cultural training set urban identities among people who live in this space to update the social knowledge of the city